PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT DUTA MEDIA INDONESIA AREA PEMATANGSIANTAR - Cahyanti, Dewi; Lie, Darwin; Efendi, Efendi; Sherly, Sherly (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The results of this study can be summarized as follows compensation is good, motivation is good and job satisfaction is also satisfied. Regression analysis result Å¶ = 13,181 + 0,542 X1 + 0,440X2, meaning there is positive influence between compensation (X1) and motivation (X2) to job satisfaction (Y) at PT Duta Media Indonesia Pematangsiantar Area. Correlation value r = 0,694 which means there is a moderately high and positive correlation between compensation, motivation and job satisfaction of employees at PT Duta Media Indonesia Pematangsiantar Area. Determination coefficient value is 0,482, meaning whether or not job satisfaction is explained by 48,2% by compensation and motivation. Hypothesis Ho rejected, meaning that compensation and motivation have a positive and significant effect on employee job satisfaction at PT Duta Media Indonesia Pematangsiantar Area.As for suggestions from the results of this study is to improve compensation should the company improve the payment system and provide better welfare to employees. To improve the motivation should the leadership should give confidence to employees to achieve high performance and eager to follow the development of technology. Meanwhile, to improve job satisfaction, the company should give more attention and give promotion to every employee who have achievement so that employees feel proud and satisfied.Â Keywords: Compensation, Motivation and Job Satisfaction